THE PROSPECTS OF THE USE OF DRUGS BASED ON RHIZOMES AND ROOTS OF URTICA DIOICA L. - E. A. Balagozyan; V. A. Kurkin; A. V. Lyamin; O. E. Pravdivtseva (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Stinging nettle (Urtica dioica L.) from the Urticaceae family is one of the popular medicinal plants. The leaves of Urtica doica L. are used in our country as a hemostatic agent. The rhizomes and roots are the base for the drugs for prostatic adenoma treatment in foreign countries. Earlier we studied acute toxicity, and diuretic activity of an extract of the rootstock with roots of Urtica doica L. We have conducted a study of antimicrobial activity of water and alcohol-water extracts from the rhizomes and roots of Urtica dioica L. The determination of a minimal inhibiting concentration was conducted by using a method of double series broth dilution. Bacillus cereus, Candida albicans, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus microorganisms were used as testing cultures. The study showed that the broth and liquid extract of the nettle, obtained on the basis of 70% ethanol do not stop the growth of microorganisms. The liquid nettle extract obtained by 40% ethanol is characterized by the weak antimicrobial activity.